2020
DOI: 10.1016/j.annonc.2020.08.164
|View full text |Cite
|
Sign up to set email alerts
|

11P Preclinical evaluation of DS-2087b, a novel and selective inhibitor of EGFR/HER2 exon 20 insertions

Abstract: Methods: Human BC tissue sections and tissue array were used to ascertain the clinical relevance of Angiomotin-p130 expressing in tumor cells and the formation of VM. We utilized MCF7 and MD-MBA-231 human tumor cells to observe VM in an orthotopic BC model and bevacizumab (anti-VEGF) was used to identify the resistance mechanism of antiangiogenic therapies in breast cancer. Later, tube formation assay was used to explore the efficacy of bevacizumab and anlotinib (anti-VEGFR,PDGFR,FGFR and c-Kit) in the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…EGFRex20ins and demonstrated selectivity over WT EGFR (36) (40). Here, we present the results of a dose-escalation phase 1/2 trial with expansion cohorts that assessed the safety, tolerability, and antitumor activity of mobocertinib in patients with metastatic EGFRex20ins-mutated NSCLC.…”
Section: Egfrex20ins Inhibitor Ds-2087b Inhibited Proliferation Of Bamentioning
confidence: 99%
“…EGFRex20ins and demonstrated selectivity over WT EGFR (36) (40). Here, we present the results of a dose-escalation phase 1/2 trial with expansion cohorts that assessed the safety, tolerability, and antitumor activity of mobocertinib in patients with metastatic EGFRex20ins-mutated NSCLC.…”
Section: Egfrex20ins Inhibitor Ds-2087b Inhibited Proliferation Of Bamentioning
confidence: 99%
“…Results from our review showed limited data on the effectiveness and/or safety of IOs in patients with Exon 20ins, however, ongoing research will further assess the impact of PD-1/PD-L1 blockade in these patients, given recent findings that patients with EGFR Exon 20ins had increased PD-L1 expression and improved outcomes compared to those with HER2 Exon 20ins [ 61 ]. In addition, several emerging compounds, such as DS-2087b [ 62 ] and BLU-945 [ 63 ], have demonstrated anti-tumour activity in preclinical studies. It should be noted that most studies identified in this SLR included a small number of patients with Exon 20ins, and there was considerable heterogeneity in the clinical and demographic characteristics of the enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…Tarloxotinib, a hypoxia-activated prodrug of a pan-HER TKI, exhibits antitumor activity in HER2 activating mutant NSCLC patient (33). DS-2087b, a selective inhibitor of EGFR/HER2 exon 20 insertions, demonstrated in vitro and in vivo inhibition in preclinical assays (34). Poziotinib demonstrated some efficacy in patients with HER2 mutations, but it was associated with high rates of WT EGFRmediated toxicity (23,35).…”
Section: Discussionmentioning
confidence: 99%